Meningkatkan Keterampilan Berbicara Siswa Melalui Video Percakapan Pendek di MTs. Al-Amin Malang - Tities Hijratur Rahmah; Juhairiyah ria (IKIP Budi Utomo Malang, 2023)
Most students have difficulty in speaking even though they already have a lot of vocabulary, the problem is that students sometimes feel afraid if they make mistakes in speaking, either because the wording is not right or they lack confidence in themselves, especially for students who feel that do not have the ability to speak English. Lack of vocabulary is also a problem according to them, because vocabulary is the first reference when we want to speak English. The students of MTs Al-Amin has some difficulties in their learning activities, one of them is because the media used by the teacher did not support them to develop their English speaking skills. The method that English teacher use is teacher center, it makes students feel bored in studying English. Beside that the researcher also found that the students are lack of vocabulary and lack confident to speak English. In this study, researcher used the Class Action Research (CAR), in which each cycle contained four stages of action, namely planning, implementing, observing, and reflecting. In collecting data, research here uses qualitative and quantitative. Qualitative data were obtained from observations and interviews with English teachers, quantitative data were obtained from the results of the pre-test and post-test. The results showed that this video can attract student’s attention to increase their learning motivation. Students can understand the material provided by the teacher, besides that students are also active in the learning process, their vocabulary also increases, they are also more confident in speaking English.